2016
DOI: 10.3832/ifor1841-009
|View full text |Cite
|
Sign up to set email alerts
|

Saproxylic beetles in non-intervention and coppice-with-standards restoration management in Meerdaal forest (Belgium): an exploratory analysis

Abstract: For many centuries, coppice-with-standards management was applied in the mixed oak stands of Meerdaal forest (Belgium). Over the last century, these stands were gradually converted to high forest. On an area of 20 ha, the coppice-with-standards management is being restored, with specific adaptations for biodiversity (conservation of dead wood and veteran trees). A survey of saproxylic beetles was performed at 8 locations in the forest, including one site within the coppice-with-standards restoration. This surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…Enkele jaren terug lieten we een doorgedreven inventarisatie van kevers uitvoeren in het Meerdaalwoud in lente en zomer van 2010 en 2011 (Vandekerkhove et al 2012;2014 Elk station bestaat uit een combinatie van een vensterval en een lijmring (= passive catch) die opgesteld zijn van april tot november. De venstervallen worden tweewekelijks geledigd.…”
Section: Proefopzetunclassified
See 1 more Smart Citation
“…Enkele jaren terug lieten we een doorgedreven inventarisatie van kevers uitvoeren in het Meerdaalwoud in lente en zomer van 2010 en 2011 (Vandekerkhove et al 2012;2014 Elk station bestaat uit een combinatie van een vensterval en een lijmring (= passive catch) die opgesteld zijn van april tot november. De venstervallen worden tweewekelijks geledigd.…”
Section: Proefopzetunclassified
“…Zo houden ze het beste contact met andere waardevolle open terreinen buiten het bos en behoudt men een voldoende grote, niet versnipperde gesloten boskern waar het bosklimaat, dat essentieel is voor heel wat soorten (kevers, maar ook nachtvlinders, slakken, …), niet wordt verstoord. (Vandekerkhove et al 2016) en de peer-reviewed paper verschenen in Iforest (Vandekerkhove et al 2015).…”
Section: Conclusiesunclassified
“…Müller et al 2008;Gossner et al 2013). The lack of broad-scale assessments of the relationship between harvesting intensity and biodiversity or biodiversity surrogates limits the generalization of these findings for larger areas (Gilliam 2002;Roberts and Zhu 2002;Vandekerkhove et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…for timber production) (Morales-Hidalgo, Oswalt, & Somanathan, 2015), debates on the effectiveness of land sparing versus land sharing concepts (Fischer et al, 2008;Grau, Kuemmerle, & Macchi, 2013) are important, and conservation strategies need to be assessed for their efficacy. It has been shown that land sharing, that is, integrative conservation approaches in European forests, can locally promote saproxylic organisms, depending on the time-scale and taxon, by restoring or retaining dead wood and old-growth elements (Brunet & Isacsson, 2009;Komonen, Kuntsi, Toivanen, & Kotiaho, 2014;Pasanen, Junninen, & Kouki, 2014;Vandekerkhove & Thomaes, 2016). However, most of these approaches are restricted to the stand scale, and landscape-wide applications of dead-wood enrichment and their evaluation with respect to biodiversity are rare.…”
mentioning
confidence: 99%